Directed Dehydration as Synthetic Tool for Generation of a New Na4SnS4 Polymorph: Crystal Structure, Na+ Conductivity, and Influence of Sb‐Substitution. Issue 36 (4th July 2022) - Hartmann, Felix; Benkada, Assma; Indris, Sylvio; Poschmann, Michael; Lühmann, Henning; Duchstein, Patrick; Zahn, Dirk; Bensch, Wolfgang
Abstract: We present the convenient synthesis and characterization of the new ternary thiostannate Na4 SnS4 (space group I 4 1 / a c d ) by directed removal of crystal water molecules from Na4 SnS4 ⋅14 H2 O. The compound represents a new kinetically stable polymorph of Na4 SnS4, which is transformed into the known, thermodynamically stable form (space group P 4 ‾ 2 1 c ) at elevated temperatures. Thermal co‐decomposition of mixtures with Na3 SbS4 ⋅9 H2 O generates solid solution products Na4− x Sn1− x Sb x S4 ( x =0.01, 0.10) isostructural to the new polymorph ( x =0). Incorporation of Sb 5+ affects the bonding and local structural situation noticeably evidenced by X‐ray diffraction, 119 Sn and 23 Na NMR, and 119 Sn Mössbauer spectroscopy. Electrochemical impedance spectroscopy demonstrates an enormous improvement of the ionic conductivity with increasing Sb content for the solid solution ( σ 25°C =2×10 −3, 2×10 −2, and 0.1 mS cm −1 for x =0, 0.01, and 0.10), being several orders of magnitude higher than for the known Na4 SnS4 polymorph. Abstract : Dehydration of Na4 SnS4 ⋅14 H2 O at moderate temperature generates the new, kinetically stabilized Na4 SnS4 polymorph exhibiting enhanced ionic conductivities compared to the thermodynamically stabilized form. Co‐decomposition with Na3 SbS4 ⋅9 H2 O enables an easy, fast, and scalable avenue to obtain the solid solution Na4− x Sn1− x Sb x S4 allowing methodical investigations of Sb‐substitution effects in these solid‐state electrolytes.